The role of strategic physiognomy in excellent marketing performance - Alaa Hussein Fadhil; Ahmed Muhammadridha Abdulrasool; Layla Mohsen Al-Hakeem; Ahmed Abdullah Amanah; Asahaq Naser Hussain (Business: Theory and Practice)
The current investigation aims to demonstrate the impact of strategic psychology, specifically empowerment, inspiration, and profound knowledge, on the achievement of exceptional performance in corporate organizations. The basic data was gathered by means of a questionnaire as a component of an analytical descriptive methodology to accomplish this aim. The Development Bank of Iraq distributed 120 questionnaires, of which 100 were returned. The primary hypothesis, which asserts that strategic physiognomy significantly impacts optimal performance, was corroborated by the study’s findings. The study came to many results, the most notable of which is that strategic Physiognomy has a favorable, substantial, and statistically significant influence on obtaining remarkable performance. The investigation ended with a set of recommendations, one of which was to raise awareness of the concept of empowerment and its role in encouraging a spirit of commitment among workers by motivating them to participate in decision-making and encouraging individual initiative, generating creative ideas, and participating in their application to achieve Excellent marketing performance.